2010
DOI: 10.1103/physrevd.81.024006
|View full text |Cite
|
Sign up to set email alerts
|

Warping, extra dimensions, and a slice ofAdSd

Abstract: Inspired by the Randall-Sundrum (RS) framework we consider a number of phenomenologically relevant model building questions on a slice of compactified AdS d for d > 5. Such spaces are interesting as they enable one to realize the weak scale via warping. We perform the Kaluza-Klein (KK) reduction for gravitons and bulk vectors in these spaces and for the case of AdS 6 consider the KK spectrum of gauge-scalars. We further obtain the KK towers for bulk fermions on a slice of AdS 7 and AdS 9 and show that the RS a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Otherwise the 4D effective couplings would be different for the two fields and hence the scattering amplitudes would not be the same. This equivalence has been found in other extra dimensional scenarios, such as when a gauge field propagates in more than five dimensions [52]. To check that the profiles do match we must find the equations of motion for the Goldstone bosons.…”
Section: A2 the Gauge-goldstone Boson Equivalence Theorem Cross Checkmentioning
confidence: 55%
See 2 more Smart Citations
“…Otherwise the 4D effective couplings would be different for the two fields and hence the scattering amplitudes would not be the same. This equivalence has been found in other extra dimensional scenarios, such as when a gauge field propagates in more than five dimensions [52]. To check that the profiles do match we must find the equations of motion for the Goldstone bosons.…”
Section: A2 the Gauge-goldstone Boson Equivalence Theorem Cross Checkmentioning
confidence: 55%
“…Such that in the unitary gauge (ξ → ∞) the Goldstone bosons become infinitely heavy and hence should be considered unphysical. From (52) and (53) it is straightforward to see that the Goldstone boson should be given by…”
Section: A2 the Gauge-goldstone Boson Equivalence Theorem Cross Checkmentioning
confidence: 99%
See 1 more Smart Citation
“…We now move to consider the scalar components of the gauge fields. For more work on gauge scalars in 6D see [38,39] or in D dimensions [22]. Firstly since the mass terms of equations (7) and ( dependant part we take ∂ i (7)−∂ 5 (8) and ∂ i (8)−∂ j (8) to get…”
Section: The Gauge Scalarsmentioning
confidence: 99%
“…The principal motivation for such a choice is that it is one of the simplest extensions to the RS model that allows the investigation of the phenomenological implications of warping the D > 5 additional dimensions and testing the robustness of the 5D phenomenology. Work has already been done looking at the phenomenology of AdS 5 × M δ [20,21] as well as AdS D [22,23,24] and for additional work on 6D RS models see for example [25,26,27,28]. The work very much continues from [29] where it was demonstrated that if the additional spaces are increasingly (decreasingly) warped towards the IR brane then the couplings of KK gauge fields propagating in the bulk will be suppressed (enhanced) relative to the zero mode couplings.…”
Section: Introductionmentioning
confidence: 99%